2014
DOI: 10.1002/nau.22700
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training versus no treatment, or inactive control treatments, for urinary incontinence in women: A short version Cochrane systematic review with meta-analysis

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(99 citation statements)
references
References 28 publications
3
79
0
17
Order By: Relevance
“…Behavioral treatments usually contain multiple components, such as urge control strategies, pelvic floor muscle training, and/or scheduled toileting [8]. Training commonly 2 Journal of Geriatrics involves biofeedback or vaginal palpation.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral treatments usually contain multiple components, such as urge control strategies, pelvic floor muscle training, and/or scheduled toileting [8]. Training commonly 2 Journal of Geriatrics involves biofeedback or vaginal palpation.…”
Section: Introductionmentioning
confidence: 99%
“…11 The evidence for PFMT is limited for mixed incontinence; nevertheless, a recent systematic review found that women treated with PMFT (for at least three months) are significantly more likely to have improvement or complete resolution of their urinary incontinence, even with mixed incontinence. 17 It is important to note that PFMT is still an appropriate first-line therapy in women with urge predominant mixed incontinence, although it is more likely for the stress incontinence component to resolve. While systemic estrogen supplement is not associated with an improvement in incontinence (and perhaps even worsens symptoms), topical vaginal estrogen has been generally shown to decrease urinary urgency, frequency, and nocturia in postmenopausal women.…”
Section: Non-surgical Treatmentmentioning
confidence: 99%
“…Ma to szczególne znaczenie w codziennej aktywności kobiet -zarówno zawodowej, jak i domowej. Według autorów widoczna jest potrzeba przygotowania obszernego programu treningu mięśni dna miednicy w profilaktyce nietrzymania moczu [36,37].…”
Section: ćWiczenia Mięśni Przepony Moczowo-płciowejunclassified